Enhancing Learning through Community Membership: Honours Students’ Perceptions of Community Membership and Its Impact on Learning - Paul Wabike (Journal of Educational Issues, 2024)
This article looks at how membership of a community impacts learning for individuals. Community membership and learning have received much attention from scholars and practitioners alike (for example, in Wolfensberger, 2012; Inkelas, Jessup-Anger, Wawrzynski, & Benjamin, 2007; Wenger, 1998). Specifically, many studies have focused on learning communities and how membership in such a community can help individual learners achieve what they are pursuing (Gabelnick et al., 1990). Using Communities-of-Practice (CoP) theory (Lave & Wenger 1991; Wenger, 1998) as a theoretical background, this study sought to understand the perceived impact of community membership on learning. The ultimate goal is to put the benefits and drawbacks of this membership in the perspective of a close-knit group of students who exist within a large school community. This study has several objectives: (1) To understand the role of the community in learning for individual members. (2) To enhance student learning that is facilitated through the presence of a community of practice. (3) To establish how a CoP can create a conducive learning environment for community members. This research article seeks to understand how community membership impacts learning through the perceptions of community members themselves. A questionnaire was sent out to 50 honours students (in the cohort 2016-2018), whereby 28 questionnaires were returned. The results show that community members experience a safe and supportive environment for their learning. The community can also be an exclusion factor from other communities, which can be counterproductive in learning. The implications of these results are discussed, and suggestions are given for school administrators who would like to use a community in enhancing learning.